2018
DOI: 10.7759/cureus.2035
|View full text |Cite
|
Sign up to set email alerts
|

A Comprehensive Review of Medical Imaging Equipment Used in Cadaveric Studies

Abstract: Medical imaging techniques have led to great advances in clinical anatomy and forensic pathology. New and emerging technologies allow healthcare professionals to view and understand the human body from different perspectives. This gives way to new and improved interventions, treatment plans, and an overall understanding of the human body. Herein, we present a comprehensive review of the various medical imaging equipment used in cadaveric studies along with their individual strengths and limitations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 51 publications
0
1
0
Order By: Relevance
“…Simonds et al [9] reported on the use of conventional radiography in cadavers to detect fractures and foreign bodies, positron emission tomography to detect tissue changes especially in Alzheimer's disease and Lewy body dementia and various uses of CT with stationary and mobile equipment. The working group reported that US has so far been underrepresented in cadaver diagnostics.…”
Section: Review Of the Literaturementioning
confidence: 99%
“…Simonds et al [9] reported on the use of conventional radiography in cadavers to detect fractures and foreign bodies, positron emission tomography to detect tissue changes especially in Alzheimer's disease and Lewy body dementia and various uses of CT with stationary and mobile equipment. The working group reported that US has so far been underrepresented in cadaver diagnostics.…”
Section: Review Of the Literaturementioning
confidence: 99%